Điều tra và qui hoạch đào tạo, bồi dưỡng công chức ngành tài chính - Nguyễn, Đức Kháng (2011)
Tác giả: Nguyễn Đức Kháng; Nguyễn Thị Bằng, TS; Phạm Mạnh Hùng, ThS; Nguyễn Văn Tạo, ThS; Đỗ Đình Lâm; Lê Thị Vân Dung; Nguyễn Văn Trúc; Tô Duy Đại -- Từ khóa: Đào tạo; Bồi dưỡng; Công chức; Tài chính